Islamic Social Welfare in DK Jakarta: Addressing Inequality and Promoting Social Cohesion - Luhuringbudi, Teguh; Putra, Purnama; Utami, Dewi Nita (Al-madinah: Journal of Islamic Civilization, 2024)
This research paper examines the role of Islamic social welfare in addressing inequality and enhancing social cohesion in Daerah Khusus Jakarta (DKJ). Using a descriptive qualitative approach, this study analyzes official statistical data from DK Jakarta in 2022-2024 through the theoretical framework of Putnam's social capital, Crenshaw's intersectionality, and Foster-Iaione's urban commons. Key findings reveal the effectiveness of the zakat-waqf network in mitigating the impact of inflation, reducing it from 3.30% (2022) to 1.98% (2024). Mosques act as centers of socio-economic innovation through programs such as "Jumu'at Berbagi" and "Digital Sharia Cooperatives". The intersectional approach in the "Ta'lim Muyassar" program effectively addresses the complexity of educational inequality. The concept of Islamic-based urban commons creates a participatory city governance model. This study produces an adaptive Islamic social welfare model, introduces "Urban Fiqh", and develops an "Islamic Urban Well-being" index. Limitations of the study include a limited geographic focus and a lack of longitudinal data. Further research is suggested to conduct comparative studies across cities and explore blockchain integration in the zakat-waqf system.